HR diagram and asteroseismic analysis of models for beta Hydri - Fernandes, J (2003)
A detailed review of the models for the star beta Hydri is done by adjusting the evolutionary sequences to the most recent bolometric, spectroscopic and astrometric data. The dependence of the solution on some of the relevant modelling parameters is analysed and the degeneracy of the solution using the HR diagram analysis discussed. Recent ground-based observations, and the forthcoming asteroseismic missions, can provide detailed oscillation spectra for this star. The seismic data can be used as a complementary constraint on the models. We analyse the seismic properties of the star and discuss the viability of using such complementary tests in order to clarify some of the degeneracy of the model solutions. Preliminary results on the fundamental parameters of beta Hydri are presented and the expected seismic behaviour of the star is described.